Through the fog of disease: the challenges faced by and vision of medical staff and patients with regard to intermittent symptom management during colorectal cancer chemotherapy - Xinchu Luo; Xi Zhang; Xi Ke; Xinyuan Yu; Yuxuan Wu; Huimin Du; Danan Lv; Dun Liu (BMC Nursing)
Abstract Background Intermittent symptom management during colorectal cancer (CRC) chemotherapy entails challenges for both medical staff and patients. This study aims to explore the factors influencing and feelings associated with symptom management with the aim of providing a reference for clinical nursing practice. Methods The researchers used a descriptive phenomenological method to conduct semistructured interviews with 19 medical professionals working in the field of oncology as well as 18 patients in April to July 2024. The interview data obtained from both parties were transcribed, coded, analysed with the aim of identifying themes and categories, described and interpreted; furthermore, the challenges entailed by and visions of symptom management extracted from the data were analysed from different perspectives. Results Four themes were obtained from the medical staff: the brilliance of the lighthouse, the fog in the dark night, the challenge of the helmsman, and the drafting of the chart. Three themes were extracted from the patients: the perception of the beacon, the symptom coping strategy, and the star map of the helmsman. Conclusions At present, intermittent symptom management during CRC chemotherapy does not meet patients’ needs. In the process of symptom management, patients are more dependent on medical staff, and medical staff are more likely to advocate common decision-making with regard to patients. However, both parties believe that developing home symptom management schemes is highly important, and they highlight the needs to focus on the challenges encountered in the process of symptom management, to overcome information barriers, to enhance communication, to strengthen education and information provision, and to help the community jointly establish a vision for a home multiple support network.